Hearing Disorders in Congenital Toxoplasmosis: A Literature Review - Corrêa, Camila de Castro; Maximino, Luciana Paula; Weber, Silke Anna Theresa (International Archives of Otorhinolaryngology, 2018)
Introduction Several studies show correlations between congenital toxoplasmosis and hearing loss, with a broad diversity of levels of hearing loss and specifications of hearing disorders.Objective To describe the studies found in the literature regarding hearing disorders in congenital toxoplasmosis.Data Synthesis A literature review was conducted on the Lilacs, SciELO, PubMed and Scopus databases by combining the following keywords: congenital toxoplasmosis and hearing. Based on this search strategy, 152 papers were found, the majority published on the Scopus and PubMed databases from 1958 to 2015. After the application of the inclusion criteria, 8 articles published between 1980 and 2015 were included in the present study.Conclusion This review showed a moderate evidence of the association between hearing disorders and congenital toxoplasmosis, which is characterized by sensorineural hearing loss. However, there are gaps in the description of the specific characteristics of the type and level of hearing loss, or of other possible disorders involved in the auditory processing.
Keywords: speech, language and hearing sciences; toxoplasmosis; toxoplasmosis, congenital; hearing; hearing disorders